Pelatihan Kerajinan Macrame dalam Pengembangan Seni Kerajinan dan Peluang Usaha - Fitriatun Fitriatun; Tania Salsabela; Lathifa Nony; Anggun Anggita; Devi Widiana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Training is an activity to improve a person's work ability in relation to economic activities. Training helps an employee understand the knowledge an organization needs to achieve its goals. Macrame craft making training was held on Saturday 20 April 2024 at Johar Market, Semarang. This service aims to provide training and utilize handicraft products into decorative products that can support welfare, namely having additional income. The method used in this training is to use theoretical methods and practical methods. Before being given material by the resource person, it was known that the Macrame Craft training participants were dominated by women. Apart from that, based on the pre-test and post-test distributed to members, it is known that the training participants already know enough about macrame.